287 A Sigma Six Approach to Improving Nephrostomy and Antegrade Stent Services After a Trust Merger – a Quality Improvement Project. (28th February 2022) - Gami, M.; McCafferty, S.
Abstract: Introduction: As hospitals merge into larger trusts there becomes a centralisation of some services. Urology relies on Interventional Radiology (IR) for Nephrostomy insertions and Anterograde stents in particular. Two lR lists run at Broomfield after centralisation. We aimed to innovate, through improving communication and appropriate prioritization of patients, to ensure patient safety and maximum utilisation of these lists. Method: We used a sigma six, DMAIC approach. Data was collected over a 30-week period. Analysis was multifaceted, focused interviews with a thematic and stakeholder analysis. Value stream maps were created to assess waste, fishbone analysis to evaluate delayed cases, and a future state map was created, implemented, and controlled. Results: Prior to the intervention, the average wait for IR was 3.66 (n = 74) days above the agreed standard of 3.5 days. Thematic analysis outlined lack of standardisation. Bottlenecks in the mapping process resulted from lack of communication. The fishbone analysis outlined organisational factors, such as rota publishing issues and task factors, such as lack of protocols and escalation clarity. The intervention was a standardised proforma, a new consultant to consultant communication channel, scan discussions at a registrar level and a point of escalation. Post intervention showed patient wait to be 1.22 day and staff satisfaction to increase 3-fold. Conclusions: The DMAIC method proved for a comprehensive assessment of improvement. Patient waiting times can be reduced in hospitals with similar experience using such methods. Future Plan-Do-Study-Act can be used to continually improve once special cause variation has been eliminated – as it likely has in this case.